Diabetes mellitus: up-to-date on antidiabetic drugs and hypoglycemic risk for the occupational physician - Orsi, Emanuela; Resi, Veronica (La Medicina del Lavoro, 2020)
Diabetes Mellitus (DM) is a complex, chronic illness requiring continuous medical care with multifactorial risk-reduction strategies beyond glycemic control. Diabetes and hyperglycemia cause chronic complications: cardiovascular disease, blindness, kidney failure and lower-limb amputation, that can lead to the exclusion of some work tasks. Diabetes drugs, as insulin or sulphonylureas, can cause hypoglycemia and the worker may be at risk of accidents. In recent years, numerous innovative drugs have become available and it is very important that the occupational physician knows their mechanism of action and their side effects since they could influence the worker’s job. Finally, the occupational physician could play a role in the prevention of type 2 diabetes: this is why it is important to know the disease, how to diagnose it and how to change the lifestyle in workers at risk.